Understanding the Political Geography of Power: the Dynamics of Space, Place and Society - Arizka Warganegara; Ahmad Nizamuddin Sulaiman (Forum Geografi, 2020)
Power is an important topics of study in the social sciences. As a concept, power has an intersubjectivity meaning. This paper analyses the various concept of power from the political geography perspective, analyzing the thoughts by four prominent and influential social scientists, Anthony Giddens, Antonio Gramsci, David Beetham, and Michel Foucault. This paper aims to explain how the concept of power has contextualized within the place, space and society’s narrative in modern-day of human life. Furthermore, the concepts of power presented by these four selected thinkers have massively influenced the notion and the discourse of the study of power nowadays. This paper argues that instead of having a different context and discourse as well as paradigm, the concepts of power by those thinkers have a similar way of thinking when looking the dynamics of space and place of the society as the basic principle of their analysis.